2019
DOI: 10.1002/adma.201905540
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Single‐Layer Photocatalysts for Methanol‐Storable Solar H2 Fuel

Abstract: The ORCID identification number(s) for the author(s) of this article can be found under https://doi.org/10.1002/adma.201905540. Molecular surfactants are widely used to control low-dimensional morphologies, including 2D nanomaterials in colloidal chemical synthesis, but it is still highly challenging to accurately control single-layer growth for 2D materials. A scalable stacking-hinderable strategy to not only enable exclusive single-layer growth mode for transition metal dichalcogenides (TMDs) selectively san… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
46
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 51 publications
0
46
1
Order By: Relevance
“…Very recently, Jia and his co-workers revealed a novel functionality of molecular surfactants as both structural directing agents and intercalation agents for control over the single-layer growth for TMDs. 32 The theoretical calculations and experimental results both successfully demonstrated that when the coverage of small organic molecules (NH 3 and H 2 S) absorbed onto the MoS 2 nanosheets reached a certain level, the binding of molecules with the MoS 2 layer could surpass the inherent interlayer binding, leading to an exclusive single-layer growth mode. Moreover, these attached molecules are likely to interact with 2D monolayered nanosheets in the subsequent selfassembly process that led the intercalation effect to happen.…”
Section: ■ Introductionmentioning
confidence: 82%
“…Very recently, Jia and his co-workers revealed a novel functionality of molecular surfactants as both structural directing agents and intercalation agents for control over the single-layer growth for TMDs. 32 The theoretical calculations and experimental results both successfully demonstrated that when the coverage of small organic molecules (NH 3 and H 2 S) absorbed onto the MoS 2 nanosheets reached a certain level, the binding of molecules with the MoS 2 layer could surpass the inherent interlayer binding, leading to an exclusive single-layer growth mode. Moreover, these attached molecules are likely to interact with 2D monolayered nanosheets in the subsequent selfassembly process that led the intercalation effect to happen.…”
Section: ■ Introductionmentioning
confidence: 82%
“…Although the trap states in perovskite NCs are known to be within the valence band/conduction band or to form shallow defect states, the improvement of the formation of core/shell structures can endow perovskite NCs with new properties, such as enhanced electron/hole separation and transfer, which are beneficial for their application in photovoltaic devices and catalysis. [ 30–33 ] Despite recent extensive research efforts being devoted to conducting the growth of core/shell perovskite NCs, consolidated understanding and strategies are yet to be established.…”
Section: Introductionmentioning
confidence: 99%
“…Two-dimensional (2D) graphene-like carbon nitride (CN) photocatalysts have been recently receiving significant attention from researchers owing to their particularly good response to visible light, relatively large specific surface area, non-toxicity, low cost, and other advantages [1][2][3][4][5][6][7][8][9][10]. In 2009, Wang et.…”
Section: Introductionmentioning
confidence: 99%